2011
DOI: 10.3109/10428194.2011.580474
|View full text |Cite
|
Sign up to set email alerts
|

Acquired immune-mediated thrombophilia in lymphoproliferative disorders

Abstract: We analyzed 66 cases of immune-mediated thrombophilia in patients with lymphoma reported in the literature. Sixty-one cases had a lupus anticoagulant, three an antibody to protein S, one to protein C, and one to ADAMTS 13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13). Lupus anticoagulants occurred in all histological subtypes of non-Hodgkin lymphoma, except mantle cell lymphoma, MALT (mucosa-associated lymphoid tissue) lymphoma, and angioimmunoblastic T-cell lymphoma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 87 publications
1
9
0
1
Order By: Relevance
“…However, on multivariate analysis, aspirin treatment was not found to have an effect on thrombosis incidence. Isolated LAC positivity might be explained with conditions as cancer [27] and infections or chronic illness [28]. These findings further support the current guidelines on LAC testing [14], in which it is stated that testing should be limited to young patients.…”
Section: Discussionsupporting
confidence: 71%
“…However, on multivariate analysis, aspirin treatment was not found to have an effect on thrombosis incidence. Isolated LAC positivity might be explained with conditions as cancer [27] and infections or chronic illness [28]. These findings further support the current guidelines on LAC testing [14], in which it is stated that testing should be limited to young patients.…”
Section: Discussionsupporting
confidence: 71%
“…Due to laboratory pitfalls in detecting LA, isolated LA positivity is of uncertain diagnostic value in patients with thrombosis and pregnancy loss or in carriers (those with positive laboratory profile but without overt disease). Isolated LA positivity might be present in other pathologic conditions such as cancer 46 and infections or chronic illness. 47 We have recently shown that as opposed to carriers of a full laboratory profile, carriers of isolated LA positivity are at low risk of thromboembolic events.…”
Section: Significance Of Positive Lupus Anticoagulantmentioning
confidence: 99%
“…Autoantibodies against the enzyme have been described in isolated cancer cases, 55,56 yet in the majority, reduced production through liver dysfunction and/or increased clearance (possibly through consumption in a prothrombotic state) has been suggested as the main cause. 11,53 However, our results suggest that low ADAMTS13 enzyme activity can lead to severe clinical consequences when exposed to anti-VEGF state.…”
Section: /2mentioning
confidence: 99%